Commercial utilization of Allo (Girardinia diversifolia) by the Rais of Sankhuwasabha for income generation - Barakoti, Tanka P; Shresta, Keshav P (Banko Janakari, 2009)
Studies carried out during 1999 and 2000 on utilization of Allo (Girardinia diversifolia L.) in the eastern hills revealed that traditional knowledge was highly used in developing commercial enterprise of this species. Surveys conducted on various aspects of this species through semi-structured interview identified that Allo has become an established income generating commodity in Bala, Sisuwa, Tamku and Mangtewa VDCs of Sankhuwasabha district. Time line showed that Allo activities were started by Kulung Rais from 1950, but increased after 1993. The community started to make fancy items, such as varieties of bags, jewellery purse to travel bags, coat cloth, and ladies items-shawl, brassier, when the outsiders took interest in Allo products. Dyeing was also practiced according to customers' demand using local plants: Majitho, Banmara, Chutro, Dar. For spinning, bamboo made hand spindle called Katuwa was used (94.8 % respondents). It is handy and easy to spin thread while walking. Weaving was done in locally made wooden handloom. Traditional processing method adopted was: green lokta- drying (2-3 days), boiling with wood ash, washing, drying, dry fibre- mixing with micaceous clay (Kamero). Wood ash was used to boil easily (39 %) and also make the fibre soft (20.8 %). No idea about the use of caustic soda instead of ash. The quantity of ash for one Dharni (2.5 kg) of lokta varied 4-24 Manas (1 Mana equals about 300g). White clay was used @ 2 kg for 2.5 kg dry lokta to make the fibre soft and easy for spinning (62.3 %). Keywords: Allo, Enterprise development,Indigenous knowledge, Rai, Sankhuwasabha. doi: 10.3126/banko.v18i1.2162 Banko Janakari, Vol. 18, No. 1, 18-24